2023
DOI: 10.3389/fnbeh.2023.1147693
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation regulates phenotypic transformation of microglia to relieve neuropathic pain induced by spinal cord injury

Abstract: ObjectiveNeuropathic pain is a common complication after spinal cord injury (SCI). Transcranial direct current stimulation (tDCS) has been confirmed to be effective in relieving neuropathic pain in patients with SCI. The aim of this study is to investigate the effect of tDCS on neuropathic pain induced by SCI and its underlying mechanism.Materials and methodsThe SCI model was induced by a clip-compression injury and tDCS stimulation was performed for two courses (5 days/each). The motor function was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…8 In our previous study, AtDCS also exhibited potential in alleviating neuropathic pain after spinal cord injury in preclinical models. 47 Therefore, we hypothesized that AtDCS may promote spared CST axon sprouting and thus lead to better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…8 In our previous study, AtDCS also exhibited potential in alleviating neuropathic pain after spinal cord injury in preclinical models. 47 Therefore, we hypothesized that AtDCS may promote spared CST axon sprouting and thus lead to better outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the organism would produce some endogenous IL-10 after SCI, this does not cover the needs of systemic and local immunoregulation for rapid termination of an excessive inflammatory storm and initiation of tissue repair and regeneration, especially reduced IL-10 expression with age ( Zaaqoq et al, 2014 ; Zhang et al, 2015 ). It is worth mentioning that certain therapies for SCI, including exercise ( Rodas et al, 2020 ), transcranial direct current stimulation ( Tan et al, 2023 ), and transplantation of mesenchymal stem cells ( Burchfield et al, 2008 ), has been shown to stimulate the production of IL-10. This suggests that the induction of IL-10 could potentially serve as a therapeutic mechanism for these treatments.…”
Section: Introductionmentioning
confidence: 99%